Keynes between the classics and Sraffa: On the issue of the numéraire - Michele Magnani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2019)
The paper sketches a coherent history of the choice of the measure standard from Adam Smith's Wealth of Nations to Sraffa's Production of Commodities. As neither the Smithian labour commanded unit nor the Ricardian-Marxian labour embodied one provide a general solution to the dilemma concerning the finding of an invariable standard, the author shows the shortcomings of both methods in an analytically rigorous way. Several years later, the largely unacknowledged fourth chapter of the General Theory once again tackles the matter of measuring aggregate values adopting a net approach and introducing an ad hoc unit. Concerned by the inherent difficulties of the operation, Keynes starts from an harsh criticism towards Pigou's notion of national dividend to end up asking himself a number of questions that makes him partially lean towards the later Sraffian approach as presented in Production of Commodities, though his stance is not fully compliant either with the premises or the aims of Piero Sraffa's theoretical framework. In the final part, a general solution based on net labour productivity is considered.
Keywords: B12; B14; B24; B51; 330; History of Economic Thought; Classical Political Economy; Post-Keynesian Economics; Choice of Units; Theory of Value